Quality Assessment of Interactive Mobile Application – Maternal and Infant Care for Tribal Birth Attendants - Rakhi Dwivedi; Akhil Dhanesh Goel; Varuna Vyas; Prem Prakash Sharma; Pratibha Singh; Kuldeep Singh (Indian Journal of Public Health)
Digital health interventions can overcome geographical barriers and prepare health-care providers for better health outcomes in rural and remote tribal areas, however, it has not been explored among traditional birth attendants (TBAs). A mobile application, “maternal and infant care” (MAI) for capacity building of tribal birth attendants was developed and its quality was evaluated using the Mobile Application Rating Scale for user’s interest in and satisfaction with the esthetics, information, and functionality. Thirteen Android user TBAs with the MAI application were piloted with the MARS checklist. Engagement, functionality, esthetics, and information quality; and one subjective quality scale having 29 items were used. The application was found to be entertaining excellent rating (mean score ± standard deviation) (4.00 ± 0.58), and scored high on performance (3.77 ± 0.93); layout design (3.85 ± 0.90); subjective quality (4.23 ± 0.93), however, scored minimum on interest; gestural design; visual appeal, etc. MAI is a user-friendly, culturally acceptable Android app that can be used for the capacity building of frontline workers.